Investigating Students’ Learning Strategies During Online Classes Using Whatsapp at The Second Grade of SMP - Miftahul Khair; Maulina Maulina; Rahmat Nasrullah (Jurnal Pendidikan dan Pengajaran, 2022)
This study aims to determine student learning strategies during online learning using WhatsApp in class II Kartika XX-6 SMP Swasta Kartika Kendari. This study uses qualitative methods with analytical techniques in the form of collection, identification, and classification. Data collection through interviews. The results showed that students used 6 strategies during the English learning process using WhatsApp to help themselves independently understand the lesson well, namely cognitive making students' ability to understand and digest online English learning through WhatsApp more optimal, metacognitive helping to develop students' abilities in learn to what extent they understand the material, related to memory helps students always remember learning material before and after starting online learning, compensatory students can understand the learning process without the help of a teacher which they learn and get from various other learning media, affective awareness of students that grows from Their deep and hidden thoughts can only be seen through the attitudes, behavior, and character of a student in the learning process, social strategies are used when students need the help of others in understanding learning materials such as friends, self-study groups or teachers.